Academic Administration of School Administrators in the Klaeng Burapha School Network under the Office of Rayong Primary Educational Service Area 2 - ประไพรัตน์ วราวุฒิ; แก้วมงคล ทรงยศ; พรมน้ำฉ่า พรธิวา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the personnel administration of schools; 2) to compare personnel administration practices; and 3) [to determine guidelines for development]. The research sample consisted of 113 civil service teachers within the Klaeng Burapha Network, obtained through simple random sampling. The research instruments included a 5-level Likert scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.60-1 and a reliability coefficient of .661, as well as structured interviews conducted with 5 school administrators. Data were analyzed using Mean, Standard Deviation, t-test, One-Way ANOVA, and Content Analysis. The research findings revealed that: • Personnel administration of schools in the Klaeng Burapha Network was overall at the highest level. • The comparative analysis of personnel administration based on personal status showed no significant differences when classified by gender and school size. However, differences based on educational attainment were statistically significant at the .05 level, and differences based on work experience were statistically significant at the .01 level. • Guidelines for personnel administration reflected a prominent organizational culture characterized by mutual support and a "family-like" atmosphere. This has a clear positive impact on morale and staff retention. However, this approach leads to a key policy recommendation: schools should develop more standardized monitoring systems and strategic planning. This is necessary to reduce reliance on individual discretion and to ensure long-term sustainability in human resource management.